PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, PERPUTARAN MODAL KERJA, LEVERAGE, DAN PERTUMBUHAN PENJUALAN TERHADAP LIKUIDITAS DITENGAH PANDEMI COVID-19 (STUDI EMPIRIS SEKTOR TRANSPORTASI DAN PERGUDANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2020) - Jesica, Jesica (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
AbstractThis research was conducted with the aim to examine the effect of cash turnover, receivable turnover, working capital turnover, leverage, and sales growth on liquidity amid the COVID-19 pandemic. This type of research used in this study is causal associative research. The population of this research are transportation and logistic sector listed on the Indonesian Stock Exchange period 2019-2020. The sampling technique is using purposive sampling technique and the analytical method used to test hypotheses is multiple regression analysis. The results show that cash turnover, receivable turnover, and leverage have negative effect on liquidity. Working capital turnover has a positive effect on liquidity and sales growth has no significant effect on liquidity.Keywords: cash turnover, receivable turnover, working capital turnover, leverage, sales growth, liquidityDAFTAR PUSTAKAAmmy, B. & Alpi, M.F. (2018). Pengaruh Perputaran Piutang dan Perputaran Modal Kerja Terhadap Likuiditas Perusahaan Otomotif dan Komponen. Jurnal Riset Finansial Bisnis, 2 (3), 135-144.Aprian, M.D., & Lestari, D.I. (2020). Pengaruh Tingkat Pertumbuhan Penjualan dan Perputaran Piutang terhadap Likuiditas Pada Perusahaan Kimia. Syntax Idea, 2(12), 1078-1092.Badan Pusat Statistik. (2021). Produk Domestik Bruto (Lapangan Usaha). Diakses dari https://www.bps.go.id/indicator/11/104/2/-seri-2010-laju-pertumbuhan-pdb-seri-2010.htmlBaskin, J. (1989). An Empirical Investigation of the Pecking Order Hypothesis Finance Management, 18, 26-35.Bisnis.com. (2021). BPS Catat Kontraksi Sektor Transportasi Paling Parah, InI Kata Ekonom. Diakses dari https://ekonomi.bisnis.com/read/20210205/98/1352771/bps-catat-kontraksi-sektor-transportasi-paling-parah-ini-kata-ekonomBrigham, E.F., & Houston, J.F. (2012). Dasar